Preparation method of hydrogenated carboxyl butadiene-acrylonitrile latex and application of hydrogenated carboxyl butadiene-acrylonitrile latex in impregnation system
Through a new preparation method, the problem of hydrogenated carboxylic nitrile rubber in the prior art lacking suitable for impregnation system was solved, and hydrogenated carboxylic nitrile latex with high hydrogenation degree and excellent adhesive properties was prepared. It is used for impregnation systems of fibers, which significantly improves the performance of the fibers and the life of the product.
Patent Information
- Application Number
- CN202411941031.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art lacks an impregnation system suitable for hydrogenated carboxylic nitrile rubber, resulting in insufficient adhesion between the fiber and the rubber, affecting the performance and life of the product.
Through a new preparation method, selective hydrogenation of carboxybutyronitrile latex is achieved, hydrogenated carboxybutyronitrile latex is prepared and applied to the impregnation system of fibers. This method does not require organic solvents and cocatalysts, and the process is simple and reduces costs and pollution.
The high hydrogenation degree and excellent adhesive properties of hydrogenated carboxybutyronitrile latex are achieved, and the tensile strength and wear resistance of the fiber are significantly improved. It is suitable for mechanical equipment and products under high strength and high temperature environments.
Smart Images

Figure BDA0005212576970000061 
Figure BDA0005212576970000071 
Figure BDA0005212576970000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation and application of hydrogenated latex, and relates to hydrogenated carboxyl nitrile latex, a preparation method thereof and application thereof in an impregnation system. Background Art
[0002] Rubber products such as tires, belts, and conveyor belts need to withstand large loads and maintain a certain shape during use. They are generally made of rubber elastomer components and high-modulus, high-strength skeleton materials. Among them, the rubber skeleton material is the main force-bearing component of rubber products. It has the function of limiting the deformation of the product, maintaining its dimensional stability, and extending the service life of the product. Common rubber skeleton materials include fibers, steel wires, etc. The fibers mainly include rayon, nylon fiber, polyester fiber, aramid fiber, and glass fiber.
[0003] The fiber is made of natural inorganic substances or carbon-containing polymers, etc., and is made by artificial spinning or direct carbonization. It has the advantages of large elastic modulus, small plastic deformation, high strength, and good heat resistance. In rubber products, the performance of the fiber skeleton material determines the performance, service life and use value. At present, the fiber skeleton material has been widely used in mechanical equipment and products in high-strength and high-temperature environments such as tires, aircraft, and rockets. In order to improve the adhesion between the fiber and rubber, impregnation treatment is generally used. At present, the more commonly used method in industry to improve the adhesion of the fiber surface is to use the resorcinol-formaldehyde-latex (RFL) system to impregnate the fiber cord. The RFL system is composed of resorcinol-formaldehyde resin (RF resin) and latex (L). RF resin is an adhesive that bonds latex and fiber together, while increasing the polarity of the dip layer and improving mechanical properties; during the vulcanization process, latex particles and rubber can be co-vulcanized to form a three-dimensional network structure of rubber, so that the latex and rubber in the dip layer form a whole and achieve firm adhesion. At present, the commonly used latexes are mainly butyl pyridine latex, natural latex, styrene butadiene latex, nitrile latex, chloroprene latex and carboxylated nitrile latex. The choice of latex is closely related to the type of fiber, the type of rubber and the vulcanization system. For example, nylon mainly uses butyl pyridine latex, and the bonding of natural rubber and styrene butadiene rubber mainly uses butyl pyridine latex, natural latex or styrene butadiene latex. However, there is currently no matching impregnation system for hydrogenated carboxylated nitrile rubber. The market gap has prompted the application of hydrogenated carboxylated nitrile latex with better wettability, higher strength and stronger polarity.
[0004] Carboxyl nitrile rubber (XNBR) is a rubber material with carboxyl groups introduced into the molecular chain of ordinary NBR. XNBR can not only use the same vulcanizing agent as ordinary NBR for cross-linking reaction, but also react with metal oxides or their salts to generate ionic cross-linking bonds due to the introduction of polar carboxyl groups. Usually, the performance advantages of XNBR can be fully exerted by combining the two forms of cross-linking. When NBR is blended and modified with PVC, rubber and plastic materials with excellent properties such as wear resistance, oil resistance, and aging resistance can be obtained. XNBR is not only widely used in the production of various high-pressure seals and wear-resistant and oil-resistant parts, but can also be used with NBR, CR or other general-purpose diene rubbers to improve the wear resistance and oil resistance of these rubbers. However, in dynamic use fields such as printing and dyeing rubber rollers, textile rubber rollers, and textile rubber rings, the product has the phenomenon of "non-wear resistance". When the requirements for elastic deformation recovery are high, this type of ordinary NBR and rubber-plastic alloy rubber cannot fully meet the use requirements.
[0005] Hydrogenated carboxyl nitrile rubber (HXNBR) is a new type of synthetic rubber developed by Lanxess of Germany. HXNBR is prepared by hydrogenating XNBR, but the hydrogenation reaction does not change the original carboxyl functional groups of XNBR, and the surface groups of the material or canvas are randomly distributed along the main chain of XNBR, just like before hydrogenation. Its structure contains carboxyl groups, which can form hydrogen bonds with the skeleton material, thereby improving its bonding properties. Compared with HNBR, HXNBR has more excellent mechanical properties, bonding properties and wear resistance, and can be used in automotive timing belts, rubber rollers for printing industry, special packers for oil wells, drill bit seals, explosion-proof devices and drill pipe scrapers.
[0006] Compared with NBR, HXNBR has greatly improved the following properties: (1) high tensile strength and elongation at a certain hardness; (2) high tensile strength, elongation and retention at 170°C; (3) excellent B-type and C-type tear strength in the range of 23°C to 170°C; (4) excellent cutting and abrasion resistance (Pick test); (5) excellent adhesion to nylon, fiber, etc. at 125°C; (6) excellent resistance to hot air aging. However, most HXNBR on the market is prepared by solution hydrogenation. The solution hydrogenation process is complicated and requires solvents during the reaction. Solvent emissions will cause environmental pollution. At the same time, the cumbersome steps lead to high costs, which limits its application in some applications. Summary of the invention
[0007] Based on the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing hydrogenated carboxyl nitrile latex, which can quickly and effectively achieve selective hydrogenation of carboxyl nitrile latex with a high degree of hydrogenation reaction; in addition, the hydrogenated carboxyl nitrile latex prepared by the method is particularly suitable for use in fiber impregnation systems.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing hydrogenated carboxyl nitrile latex, the method comprising:
[0010] A) mixing a portion of the carboxylated nitrile latex and a Grubbs II catalyst to obtain a latex mixture;
[0011] B) mixing the latex mixture with the remaining carboxylated nitrile latex, and performing a hydrogenation reaction in the presence of hydrogen to obtain the hydrogenated carboxylated nitrile latex.
[0012] In the present invention, the source of the carboxylated nitrile latex is not particularly limited and can be any commercially available one.
[0013] In the present invention, the hydrogenation reaction does not require a promoter, the hydrogenation conditions are mild, and the cost can be reduced.
[0014] In the present invention, the hydrogenation reaction does not require the use of an organic solvent, the process is simple, and pollution is reduced.
[0015] According to an embodiment of the present invention, the acrylonitrile content in the carboxylated nitrile latex is 15-50 wt %, preferably 20-40 wt %.
[0016] According to an embodiment of the present invention, the carboxyl nitrile latex has a carboxyl content of 1-30%, preferably 2-15%.
[0017] According to an embodiment of the present invention, the solid content of the carboxylated nitrile latex is 8-35 wt %, preferably 10-30 wt %.
[0018] According to an embodiment of the present invention, the average particle size of the polymer particles in the carboxylated nitrile latex is 10-200 nm, preferably 40-150 nm.
[0019] According to an embodiment of the present invention, the volume ratio of the carboxylated nitrile latex in step A) to the carboxylated nitrile latex in step B) is 0.5-1.5:0.5-1.5.
[0020] According to an embodiment of the present invention, in step A), the mass of the Grubbs II catalyst accounts for 0.01-0.1wt% of the mass of the carboxylated nitrile rubber in the carboxylated nitrile latex, exemplarily 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt% or 0.1wt%.
[0021] According to an embodiment of the present invention, in step B), after the latex mixture and the remaining carboxyl nitrile latex are mixed, they are degassed; preferably, the degassing temperature is 20-40°C; preferably, the degassing time is 20-60min; preferably, the degassing pressure is 0.1-2MPa; preferably, the degassing is performed using nitrogen.
[0022] According to an embodiment of the present invention, in step B), the temperature of the hydrogenation reaction is 80-110°C; preferably, the time of the hydrogenation reaction is 1-24h, preferably 2-8h, for example 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0023] According to an embodiment of the present invention, in step B), the pressure of the hydrogen is 5.5-7.0 MPa, for example, 5.5 MPa, 6 MPa, 6.5 MPa or 7 MPa.
[0024] As an exemplary embodiment of the present invention, the preparation method of the hydrogenated carboxyl nitrile latex specifically comprises the following steps:
[0025] A) mixing a portion of the carboxylated nitrile latex and a Grubbs II catalyst to obtain a latex mixture;
[0026] B) mixing the latex mixture and the remaining carboxyl nitrile latex, degassing, heating to 80-110° C.; adding hydrogen, and carrying out hydrogenation reaction at 80-110° C. and a hydrogen pressure of 5.5-7.0 MPa to obtain hydrogenated carboxyl nitrile latex.
[0027] Preferably, the hydrogenation reaction is carried out in stages; the heating rate of each stage is the same or different, and illustratively, the heating rate is 0.1-10°C / min.
[0028] The invention also provides the hydrogenated carboxyl nitrile latex prepared by the method.
[0029] According to an embodiment of the present invention, the hydrogenation degree of the hydrogenated carboxylated nitrile latex is 20-99%, preferably 60-99%; the acrylonitrile content is preferably 20-40 wt%; and the carboxyl content is preferably 1-25%.
[0030] The present invention also provides an impregnation system for fiber surface treatment, wherein the raw materials of the impregnation system include:
[0031] 1) Phenolic resin;
[0032] 2) the above-mentioned hydrogenated carboxyl nitrile latex or a modified product thereof; and
[0033] 3) pH adjuster.
[0034] According to the present invention, the pH regulator makes the pH of the system be 9-11. Exemplarily, the pH regulator is an aqueous ammonia solution; preferably, the concentration of the aqueous ammonia solution is 15-30%, for example, 25%.
[0035] According to an embodiment of the present invention, the impregnation system includes a reactant of the phenolic resin and the hydrogenated carboxylated nitrile latex or a modified product thereof.
[0036] According to an embodiment of the present invention, the phenol in the phenolic resin can be selected from at least one of resorcinol, phenol, cresol, xylenol, bisphenol A, para-chlorophenol, etc.; specifically, the aldehyde in the phenolic resin can be selected from at least one of formaldehyde, furfural, furfural, acetaldehyde, polyformaldehyde, etc.; also specifically, the phenolic resin is resorcinol-formaldehyde resin.
[0037] Exemplarily, the phenolic resin is prepared by raw materials including the following components in parts by weight:
[0038] Phenol (specifically, resorcinol) 1-5 parts; preferably 2-4 parts;
[0039] Aldehyde (specifically, formaldehyde) 2-8 parts, preferably 3-5 parts;
[0040] 50-60 parts of water (specifically deionized water); and
[0041] Alkali (specifically selected from sodium hydroxide, for example) 0.1-5 parts.
[0042] According to an embodiment of the present invention, the formaldehyde is added in the form of a formaldehyde solution, and the concentration of the formaldehyde solution is 20-50%, for example, 37%.
[0043] According to an embodiment of the present invention, in the raw materials of the impregnation system, the hydrogenated carboxyl nitrile latex or its modifier is 50-150 parts by weight, preferably 56-120 parts by weight.
[0044] According to an embodiment of the present invention, the raw materials of the impregnation system further include a stabilizer; preferably, the stabilizer is 0.3-1 part by weight, preferably 0.5-0.8 part by weight.
[0045] According to an embodiment of the present invention, the stabilizer is selected from one or more of sulfate ester salts, sulfonates, carboxylates, fatty alcohols, etc. Specifically, it can be selected from DuPont stabilizer BK263.
[0046] According to an embodiment of the present invention, the raw materials for forming the modified product of the hydrogenated carboxyl nitrile latex include: the above-mentioned hydrogenated carboxyl nitrile latex and nano metal oxide.
[0047] According to an embodiment of the present invention, in the raw materials for forming the modified product of the hydrogenated carboxyl nitrile latex, the nano metal oxide is 0.5-5 parts by weight, preferably 1-2.5 parts by weight.
[0048] According to an embodiment of the present invention, the nano metal oxide is, for example, at least one selected from nano zinc oxide, magnesium oxide, titanium dioxide and the like.
[0049] In the present invention, the nano metal oxide has good stability in the hydrogenated carboxyl nitrile latex, has obvious reinforcing effect on the hydrogenated carboxyl nitrile latex, and can promote the cross-linking reaction of the hydrogenated carboxyl nitrile latex.
[0050] According to an embodiment of the present invention, the raw materials for forming the modified product of the hydrogenated carboxylated nitrile latex further include a wetting agent; preferably, in parts by weight, the wetting agent is 0.3-0.5 parts, exemplarily 0.3, 0.4 or 0.5 parts. Specifically, the wetting agent can be selected from OT75.
[0051] According to an embodiment of the present invention, the raw materials for forming the modified product of the hydrogenated carboxyl nitrile latex also include a thickener; preferably, the thickener is 0.1-0.8 parts by weight, preferably 0.2-0.5 parts by weight.
[0052] According to an embodiment of the present invention, the thickener is selected from one or more of alginic acid, sodium carboxymethyl cellulose, sodium phosphate, polyacrylamide, polyacrylic acid, etc. Specifically, it can be selected from polyacrylic acid 2080W.
[0053] According to an embodiment of the present invention, the modified substance of the hydrogenated carboxyl nitrile latex is prepared by the following method: 100 parts of the above-mentioned hydrogenated carboxyl nitrile latex (for example, the above-mentioned hydrogenated carboxyl nitrile latex with a degree of hydrogenation of 95%) are used, 0.5-5 parts (for example, 1-2.5 parts) of nano metal oxide and 0.3-0.5 parts of wetting agent are added thereto in sequence, and magnetic stirring is performed at 30-50°C (specifically 40°C) and 400-800rpm (specifically 600rpm) for a certain time (such as 2 hours), and then 0.1-0.8 parts (for example, 0.2-0.5 parts) of thickener are added, and magnetic stirring is continued at room temperature of 150-200rpm for a certain time (such as half an hour), and finally ultrasonic defoaming treatment is performed in a water bath, and the mixture is allowed to stand for defoaming to obtain the modified substance.
[0054] During the preparation of the impregnation system of the present invention, a certain dispersion method (such as high-speed dispersion or ultrasonic treatment) is used to enable each raw material to be well dispersed in the impregnation system and to remain stable for a long time.
[0055] According to an embodiment of the present invention, the system is prepared from raw materials including the following component 1, in parts by weight:
[0056]
[0057]
[0058] According to an embodiment of the present invention, the degree of hydrogenation of the hydrogenated carboxylated nitrile latex is preferably 60-99%.
[0059] According to an embodiment of the present invention, the raw materials of the impregnation system further include a silane coupling agent type curing agent; specifically, in parts by weight, the curing agent is 0.5-3 parts, preferably 0.5-2 parts.
[0060] According to an embodiment of the present invention, the silane coupling agent type curing agent can be at least one of aminosilane (such as KH-792), phenylsilane (such as ND-42), epoxy silane (such as KH-540), and isocyanate silane.
[0061] According to an embodiment of the present invention, the raw materials of the impregnation system further include a thickener, and the thickener is 0.1-0.8 parts by weight, preferably 0.2-0.5 parts by weight.
[0062] According to an embodiment of the present invention, the raw materials of the impregnation system further include a wetting agent, and the wetting agent is 0.3-0.5 parts by weight.
[0063] In the present invention, the silane coupling agent type curing agent contains a chemical functional group (Si-O-Si bond) that can form a covalent bond with the silanol group on the fiber surface; in addition, the silane coupling agent type curing agent also contains a carboxyl group, a diene group, a hydroxyl group, an amine group, an alcohol group, etc. (may be several of them) to bond with the polymer molecules to obtain a good interface bond. The impregnation embodiment is simple to prepare, and a small amount of silane coupling agent type curing agent can improve the strength of the fiber, and the hydrogenated carboxyl nitrile latex vulcanization can be promoted without high temperature, while increasing the binding sites of the hydrogenated carboxyl nitrile latex and the fiber.
[0064] According to an embodiment of the present invention, the system is prepared from raw materials including the following components, in parts by weight:
[0065]
[0066]
[0067] According to an embodiment of the present invention, the raw materials of the impregnation system further include nanofibers; specifically, in parts by weight, the nanofibers are 1-5 parts, preferably 2-3 parts.
[0068] According to an embodiment of the present invention, the raw materials of the impregnation system further include a silane coupling agent; specifically, in parts by weight, the silane coupling agent is 0.5-5 parts, preferably 1-3 parts.
[0069] According to an embodiment of the present invention, the silane coupling agent can be at least one of an aminosilane coupling agent, an epoxysilane coupling agent, an isocyanate silane coupling agent, and a titanate coupling agent, such as KH550, KH560, KH570, KH580, NDZ-102, and A-151.
[0070] In the present invention, nanofiber and silane coupling agent are used as bridging agents to form a fiber-coupling agent-RFL structure, and the interlayer interface is more stable. Nanofiber has the advantages of higher elastic modulus, better thermal stability and lower thermal expansion coefficient, so nanofiber is added to hydrogenated carboxyl nitrile latex as a reinforcing material. In addition, nanofiber and fiber (or fiber matrix) have hydroxyl groups that can form hydrogen bonds, and can form a molecular chain interpenetrating structure.
[0071] According to an embodiment of the present invention, the system is prepared from raw materials including the following three components, in parts by weight:
[0072]
[0073]
[0074] According to an embodiment of the present invention, the raw materials of the impregnation system further include rubber latex emulsion; specifically, in parts by weight, the rubber latex emulsion is 5-100 parts, preferably 30-60 parts, for example 30 parts.
[0075] According to an embodiment of the present invention, the rubber latex emulsion is selected from at least one of acrylate, acrylamide and itaconate. The solid content of the rubber latex emulsion is 20-30%.
[0076] According to an embodiment of the present invention, the raw materials of the impregnation system further include a silane coupling agent type curing agent; specifically, in parts by weight, the silane coupling agent type curing agent is 0.5-3 parts, preferably 1-2 parts.
[0077] In the present invention, a rubber latex emulsion optionally containing carboxyl and amide bonds is compounded with a hydrogenated carboxyl nitrile latex, the hydrogenated carboxyl nitrile latex provides flexibility, the hydrogenated carboxyl nitrile latex emulsion undergoes a cross-linking reaction during the curing process, the rubber latex emulsion provides hardness, and an impregnation liquid system with adjustable tensile strength is obtained by changing the ratio of the rubber latex emulsion and the silane coupling agent type curing agent. The rubber latex emulsion with amide and carboxyl functional groups is selected for compounding to have good adhesion to the fiber.
[0078] According to an embodiment of the present invention, the system is prepared from raw materials including the following four components, in parts by weight:
[0079]
[0080]
[0081] The present invention also provides a method for preparing the impregnation system, which comprises: mixing various raw materials and reacting them to obtain the impregnation system.
[0082] Specifically, the preparation method of the impregnation system based on the above component 1 includes:
[0083] (a1) preparing resorcinol-formaldehyde resin;
[0084] (a2) mixing the above-mentioned hydrogenated carboxyl nitrile latex, nano metal oxide, stabilizer, wetting agent and thickener to obtain the hydrogenated carboxyl nitrile latex enhanced by the nano metal oxide;
[0085] (a3) mixing the resorcinol-formaldehyde resin in step (a1) and the hydrogenated carboxylated nitrile latex reinforced with nano-metal oxide in step (a2), adding an aqueous ammonia solution to adjust the pH value of the system to 9-11, and reacting to obtain an impregnation system based on component one.
[0086] In step (a1) of the present invention, the preparation of the resorcinol-formaldehyde resin adopts a method known in the art. For example, the preparation method of the resorcinol-formaldehyde resin is as follows: resorcinol, water and sodium hydroxide are mixed and reacted, and then formaldehyde is added to the mixed solution to react, and the pH value of the reaction system is set to between 7 and 8 to obtain the resorcinol-formaldehyde resin.
[0087] According to an embodiment of the present invention, in step (a3), the mass ratio of the resorcinol-formaldehyde resin to the nano-metal oxide-reinforced hydrogenated carboxyl nitrile latex is 100:5-20.
[0088] Specifically, the preparation method of the impregnation system based on the above-mentioned component 2 includes:
[0089] (b1) preparing resorcinol-formaldehyde resin;
[0090] (b2) mixing the hydrogenated carboxyl nitrile latex, a silane coupling agent type curing agent, a wetting agent, a stabilizer, a thickener and a solvent to obtain a hydrogenated carboxyl nitrile latex modified by a silane coupling agent type curing agent;
[0091] (b3) mixing the resorcinol-formaldehyde resin in step (b1) and the hydrogenated carboxyl nitrile latex modified by the silane coupling agent type curing agent in step (b2), and adding an ammonia solution to adjust the pH of the system to 9-11, thereby obtaining an impregnation system based on component two.
[0092] According to an embodiment of the present invention, in step (b2), the mass ratio of the resorcinol-formaldehyde resin to the hydrogenated carboxyl nitrile latex modified by the silane coupling agent type curing agent is 100:5-20.
[0093] According to an embodiment of the present invention, in step (b3), the solvent is selected from one or more of ethanol, acetone, methyl ethyl ketone, methanol, and tetrahydrofuran.
[0094] Specifically, the preparation method of the impregnation system based on the above-mentioned component three includes:
[0095] (c1) preparing resorcinol-formaldehyde resin;
[0096] (c2) mixing the nanofibers, a silane coupling agent and a solvent to obtain modified nanofibers; and mixing the modified nanofibers with the hydrogenated carboxyl nitrile latex to obtain hydrogenated carboxyl nitrile latex reinforced with the modified nanofibers;
[0097] (c3) Mixing the resorcinol-formaldehyde resin in step (c1) and the modified nanofiber-reinforced hydrogenated carboxyl nitrile latex in step (c2), and adding an aqueous ammonia solution to adjust the pH of the system to 9-11, thereby obtaining an impregnation system based on component three.
[0098] According to an embodiment of the present invention, in step (c3), the mass ratio of the resorcinol-formaldehyde resin to the modified nanofiber reinforced hydrogenated carboxyl nitrile latex is 100:5-20.
[0099] According to an embodiment of the present invention, in step (c2), the solvent is selected from one or more of ethanol, acetone, methyl ethyl ketone, methanol, and tetrahydrofuran.
[0100] Specifically, the preparation method of the impregnation system based on the above-mentioned component four includes:
[0101] (d1) preparing resorcinol-formaldehyde resin;
[0102] (d2) mixing the rubber latex emulsion, the hydrogenated carboxyl nitrile latex, a stabilizer and a silane coupling agent type curing agent to obtain a mixed latex;
[0103] (d3) mixing the resorcinol-formaldehyde resin in step (d1) and the mixed latex in step (d2), and adding an aqueous ammonia solution to adjust the pH of the system to 9-11, thereby obtaining an impregnation system based on component four.
[0104] According to an embodiment of the present invention, in step (d3), the mass ratio of the resorcinol-formaldehyde resin to the mixed latex is 100:5-20.
[0105] The preparation of the resorcinol-formaldehyde resin in steps (b1), (c1) and (d1) of the present invention is the same as that in step (a1).
[0106] The present invention also provides a fiber processing method, which comprises: placing a fiber matrix in the impregnation system.
[0107] In the present invention, the fiber matrix may be any fiber known in the art.
[0108] The beneficial effects of the present invention are:
[0109] (1) The preparation of the hydrogenated carboxyl nitrile latex of the present invention can quickly and effectively achieve the selective hydrogenation of the carboxyl nitrile latex without using any organic solvent, the reaction conditions are mild, the degree of hydrogenation reaction is high, no organic solvent is involved in the hydrogenation process, and no auxiliary agent (such as a co-catalyst) is added. No post-treatment process is required, and the hydrogenation process is green and environmentally friendly. At the same time, the amount of catalyst used is small, which effectively saves production costs.
[0110] (2) The method for preparing the hydrogenated carboxylated nitrile latex provided by the present invention can make the hydrogenation degree of the hydrogenated carboxylated nitrile latex exceed 90%, and the hydrogenation reaction can be completed within a range of no more than 8 hours.
[0111] (3) The present invention discloses a series of impregnation liquid systems for fiber surface treatment using hydrogenated carboxyl nitrile rubber latex, which can provide excellent adhesion between the fiber and the hydrogenated carboxyl nitrile rubber interface and greatly improve the tensile strength of the fiber. DETAILED DESCRIPTION
[0112] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0113] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0114] Embodiment 1:
[0115] The preparation method of hydrogenated carboxyl nitrile latex is as follows:
[0116] A 300mL stainless steel high-pressure reactor with a temperature control device, a stirrer and a hydrogen addition point was used. A carboxylated nitrile rubber latex with an acrylonitrile content of 33wt%, a solid content of 23.6% and a carboxyl content of 6% was used, and the average diameter of the polymer particles in the carboxylated nitrile rubber latex was 88nm. At room temperature, 50mL of the above-mentioned carboxylated nitrile rubber latex and Grubbs II catalyst were loaded into the reactor, and after mixing, 50mL of the above-mentioned carboxylated nitrile rubber latex was continued to be added, wherein the mass percentage of Grubbs II catalyst and carboxylated nitrile rubber in the latex was 0.02%. The latex was then degassed with nitrogen, the degassing temperature was 40°C, the degassing time was 20min, and the degassing pressure was 1MPa. Two sections of heating were then used, with the first section heating to 80°C at 5°C / min, and the second section heating to 90°C at 1°C / min. The hydrogenation reaction was carried out at 90°C and a hydrogen pressure of 800 psi (5.52 MPa) for 7 hours to obtain a hydrogenated carboxylated nitrile rubber (HXNBR) latex with a hydrogenation degree of 95%. After the reaction, the reacted latex was coagulated using ethanol to obtain the hydrogenated carboxylated nitrile rubber (HXNBR).
[0117] The preparation method of the nano-metal oxide enhanced RFL impregnation system (i.e., the impregnation system containing component one) is as follows:
[0118] Step (1) Preparation of resorcinol-formaldehyde resin (RF resin)
[0119] Place a three-necked flask in a constant temperature water bath at 25°C, add 2 parts of resorcinol and 50 parts of deionized water, set the stirring speed to 200r / min, after the resorcinol is completely dissolved, weigh 0.7 parts of NaOH solution and slowly add it drop by drop into the three-necked flask, react for 10 minutes, then weigh 3.5 parts of formaldehyde and slowly add it drop by drop, control the mass ratio of NaOH to resorcinol to 3 / 100, the solid content of the system to 5.6%, the pH value to be between 7-8, react for 6 hours, and obtain RF resin.
[0120] Step (2) Preparation of Nano-Metal Oxide Reinforced Hydrogenated Carboxyl Nitrile Rubber Latex (HXNBR Latex)
[0121] 100 parts of HXNBR latex with a hydrogenation degree of 95% are added with 2.5 parts of zinc oxide (or magnesium oxide, titanium oxide) dispersion, 0.5 parts of wetting agent OT75, and 1 part of stabilizer DuPont stabilizer BK263 in sequence, and magnetically stirred at 40°C and 600rpm for 2 hours, then 0.5 parts of thickener polyacrylic acid 2080W are added, and magnetic stirring is continued at room temperature at 150-200rpm for half an hour, and finally ultrasonic defoaming treatment is performed in a water bath, and the mixture is allowed to stand for defoaming to obtain a hydrogenated carboxyl nitrile latex reinforced with nano metal oxide.
[0122] Step (3) Preparation of Nano-Metal Oxide Enhanced Hydrogenated Carboxyl Nitrile Latex Test Film
[0123] The above 15 ml of nano-metal oxide-enhanced hydrogenated carboxyl nitrile latex was poured into a 10 cm × 10 cm × 0.1 cm polytetrafluoroethylene mold and placed in a 60°C oven to dry for 48 hours. Finally, the film was peeled off and cut into dumbbell-shaped pieces with a length of 150 cm and a width of 2.5 cm. The tensile strength and elongation at break were tested according to GBT-13022-1991 standard. The data are shown in Table 1.
[0124] Step (4) Preparation of RFL impregnation solution
[0125] The RF resin prepared in step (1) and the nano-metal oxide-reinforced HXNBR latex prepared in step (2) are used to synthesize an RFL impregnation solution under alkaline conditions (using 25% ammonia water to adjust the pH to 9-10), and the mass ratio of the RF resin to the nano-metal oxide-reinforced HXNBR latex is adjusted to 100:15.
[0126] Step (5) RFL impregnation liquid treatment fiber
[0127] The glass fiber yarn is impregnated with the RFL impregnation liquid prepared in step (4). First, a certain length of glass fiber yarn is measured and placed in an impregnation tank, and then the RFL impregnation liquid is added to completely cover the glass fiber yarn. The impregnation time is controlled to be 60 seconds, and then the glass fiber yarn is dried at room temperature and rolled up, and finally dried at 120°C for 5 minutes to obtain the impregnated glass fiber (i.e., impregnated glass fiber), which is sealed and stored away from light.
[0128] Step (6) Testing the strength of glass fiber treated with RFL impregnation liquid
[0129] According to GB / T2942-2009, a flat vulcanizer is used to prepare glass fiber cords (i.e. impregnated glass fiber) and chloroprene rubber matrix into standard H-type specimens. The specific operation is: cut the rubber strip according to the size of the mold cavity, then put the mold on the flat vulcanizer for preheating, put the treated glass fiber cords and chloroprene rubber into the mold, and vulcanize on the flat vulcanizer. The vulcanization process conditions are: 160℃, vulcanization time 15min, vulcanization pressure 8MPa. An electronic tensile machine is used to perform H extraction test on the H specimen. Five parallel samples are tested for each sample, and the test results are averaged. The test conditions are: the fixture movement speed is 100mm / min, the experimental temperature is 23±2℃, and the relative humidity is 50±5%.
[0130] Embodiment 2:
[0131] The preparation method of the hydrogenated carboxyl nitrile rubber latex is shown in Example 1.
[0132] The preparation method of the silane coupling agent type curing agent modified RFL dipping system is as follows:
[0133] Step (1) is the same as in Example 1
[0134] Step (2) Preparation of 95% hydrogenated HXNBR latex modified with silane coupling agent curing agent
[0135] 2.1 Aminosilane type curing agent modified HXNBR latex
[0136] Dissolve 1 ml of KH-792 in 19 ml of acetone and stir magnetically for 30 minutes to prepare a 5% curing agent dispersion. Then take 10 ml of the curing agent dispersion and add 50 ml of HXNBR with a solid content of 40% and a hydrogenation degree of 95%, and then add 0.5 parts of wetting agent OT75, 1 part of stabilizer American DuPont stabilizer BK263, and 0.5 parts of thickener polyacrylic acid 2080W in sequence, and stir at a low speed at 30°C for 1 hour.
[0137] 2.2 Phenylsilane type curing agent modified HXNBR latex
[0138] Dilute 10ml of anhydrous ethanol to 50ml of diluted solution, then take 1ml of curing agent ND-42 and dissolve it in 19ml of ethanol solution and stir magnetically for 30 minutes. Finally, take 10ml of curing agent dispersion and add 50ml of HXNBR with a solid content of 40% and a hydrogenation degree of 95%, then add 0.5 parts of wetting agent OT75, 1 part of American DuPont stabilizer BK263, and 0.2-0.5 parts of thickener acrylic polymer 2080W in turn, and stir at low speed at room temperature for 1h.
[0139] 2.3 Epoxysilane type curing agent modified HXNBR latex
[0140] Dissolve 1 ml of KH-540 in 19 ml of acetone and stir magnetically for 30 minutes to prepare a 5% curing agent dispersion. Then take 10 ml of the curing agent dispersion and add 50 ml of HXNBR with a solid content of 40% and a hydrogenation degree of 95%, and then add 0.5 parts of wetting agent OT75, 1 part of DuPont stabilizer BK263, and 0.5 parts of thickener acrylic polymer 2080W in sequence, and stir at a low speed at 30°C for 1 hour.
[0141] Steps (3-6) are the same as in Example 1 above.
[0142] Embodiment 3:
[0143] The preparation method of the hydrogenated carboxyl nitrile rubber latex is shown in Example 1.
[0144] The preparation method of the silane coupling agent modified nanofiber reinforced RFL impregnation system is as follows:
[0145] Step (1) is the same as in Example 1
[0146] Step (2) Preparation of modified nanofiber reinforced HXNBR latex
[0147] Add nanocrystalline cellulose and a certain amount of anhydrous ethanol to a three-necked flask, stir evenly at room temperature, add 25% ammonia water to adjust the pH to 6-7, add 2 parts of silane coupling agent KH550 (or KH560, KH570, KH580, NDZ-102, A-151), condense and reflux for 2 hours, and then centrifuge and wash to obtain modified nanocrystalline cellulose. Prepare a 10% concentration of modified nanocrystalline cellulose suspension (MNCC) with deionized water for standby use. At 25°C, blend 3% mass fraction of MNCC with 95% hydrogenation degree HXNBR latex solution, place the mixed solution under a high-speed homogenizer for 5 minutes to disperse it evenly, and obtain modified nanofiber reinforced hydrogenated carboxyl nitrile latex.
[0148] Steps (3-6) are the same as in Example 1
[0149] Embodiment 4:
[0150] The preparation method of the hydrogenated carboxyl nitrile rubber latex is shown in Example 1.
[0151] The preparation method of the rubber latex emulsion compounded RFL dipping system (i.e., the dipping system containing component four) is as follows:
[0152] Step (1) is the same as in Example 1
[0153] Step (2) Preparation of latex compounding
[0154] Take 30 parts of itaconate (or acrylate, acrylamide) emulsion, add 100 parts of HNXBR latex with 95% hydrogenation degree, then add 1 part of DuPont stabilizer BK263, stir at room temperature for 30 minutes. Then add 2 parts of silane coupling agent curing agent KH-792, stir at high speed for 10 minutes, and heat during stirring as needed.
[0155] Steps (3-6) are the same as in Example 1 above.
[0156] The HXNBR prepared in Example 1 and the latex test film prepared in step (3) of Examples 1-4 were subjected to tensile tests. The test results are shown in Table 1.
[0157] Table 1
[0158] Example Tensile strength / Mpa Elongation at break / % HXNBR 5 560 1 30 482 2 12 320 3 16 305 4 10 286
[0159] The impregnated glass fibers in step (5) of the above Examples 1-4 were subjected to a tensile test. The test results are shown in Table 2.
[0160] Table 2
[0161]
[0162]
[0163] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenated carboxyl nitrile latex, characterized in that: The method comprises: A) mixing a portion of the carboxylated nitrile latex and a Grubbs II catalyst to obtain a latex mixture; B) mixing the latex mixture with the remaining carboxylated nitrile latex, and performing a hydrogenation reaction in the presence of hydrogen to obtain the hydrogenated carboxylated nitrile latex.
2. The method according to claim 1, characterized in that The volume ratio of the carboxylated nitrile latex in step A) to the carboxylated nitrile latex in step B) is 0.5-1.5:0.5-1.
5. Preferably, in step A), the mass of the Grubbs II catalyst accounts for 0.01-0.1 wt % of the mass of the carboxylated nitrile rubber in the carboxylated nitrile latex. Preferably, in step B), the temperature of the hydrogenation reaction is 80-110° C.; and the time of the hydrogenation reaction is 1-24 h. Preferably, in step B), the pressure of the hydrogen is 5.5-7.0 MPa.
3. The hydrogenated carboxyl nitrile latex prepared by the method according to claim 1 or 2. Preferably, the hydrogenation degree of the hydrogenated carboxylated nitrile latex is 20-99%, the acrylonitrile content is 20-40 wt%; and the carboxyl content is 1-25%.
4. An impregnation system for fiber surface treatment, characterized in that: The raw materials of the impregnation system include: 1) Phenolic resin; 2) the hydrogenated carboxyl nitrile latex or a modified product thereof according to claim 3; and 3) pH adjuster.
5. The impregnation system according to claim 4, characterized in that The raw materials of the impregnation system also include a stabilizer. Preferably, the stabilizer is 0.3-1 part by weight. Preferably, the raw materials for forming the modified product of the hydrogenated carboxylated nitrile latex include a wetting agent; preferably, the wetting agent is 0.3-0.5 parts by weight. Preferably, the raw materials for forming the modified product of the hydrogenated carboxyl nitrile latex also include a thickener; preferably, the thickener is 0.1-0.8 parts by weight.
6. The impregnation system according to claim 5, characterized in that The raw materials for forming the modified product of the hydrogenated carboxyl nitrile latex include: the hydrogenated carboxyl nitrile latex as claimed in claim 3 and nano metal oxide. Preferably, in the raw materials for forming the modified product of the hydrogenated carboxylated nitrile latex, the nano metal oxide is 0.5-5 parts by weight. Preferably, the nano metal oxide is selected from at least one of nano zinc oxide, magnesium oxide and titanium dioxide.
7. The impregnation system according to claim 4, characterized in that The raw materials of the impregnation system also include a silane coupling agent type curing agent; preferably, the curing agent is 0.5-3 parts by weight. Preferably, the silane coupling agent type curing agent is at least one of aminosilane (such as KH-792), phenylsilane (such as ND-42), epoxy silane (such as KH-540), and isocyanate silane. Preferably, the raw materials of the impregnation system further include a thickener; preferably, the thickener is 0.1-0.8 parts by weight. Preferably, the raw materials of the impregnation system also include a wetting agent; preferably, the wetting agent is 0.3-0.5 parts by weight.
8. The impregnation system according to claim 4, characterized in that The raw materials of the impregnation system also include nanofibers; preferably, the nanofibers are 1-5 parts by weight. Preferably, the raw materials of the impregnation system further include a silane coupling agent; preferably, the silane coupling agent is 0.5-5 parts by weight.
9. The impregnation system according to claim 4, characterized in that The raw materials of the impregnation system also include rubber latex emulsion; preferably, the rubber latex emulsion is 5-100 parts by weight. Preferably, the rubber latex emulsion is selected from at least one of acrylate, acrylamide and itaconate. Preferably, the raw materials of the impregnation system further include a silane coupling agent type curing agent; preferably, the silane coupling agent type curing agent is 0.5-3 parts by weight.
10. A method for preparing an impregnation system according to any one of claims 4 to 9, characterized in that: The method comprises the following steps: mixing and reacting various raw materials to obtain the impregnation system.
11. A method for processing fiber, characterized in that: include: The fiber matrix is placed in the impregnation system according to any one of claims 4-9.